Accumulation and Competition Amongst Deformed Wing Virus Genotypes in Naïve Australian Honeybees Provides Insight Into the Increasing Global Prevalence of Genotype B - Norton, Amanda M.; Remnant, Emily J.; Buchmann, Gabriele; Beekman, Madeleine (Frontiers in Microbiology, 2020)
Honeybee colony deaths are often attributed to the ectoparasitic mite Varroa destructor and deformed wing virus (DWV), vectored by the mite. In the presence of V. destructor both main genotypes (DWV-A and DWV-B) have been correlated with colony loss. Studies show that DWV-B is the most prevalent genotype in the Europe. More recently DWV-B has increased in prevalence in the United States. The increasing prevalence of DWV-B at the expense of DWV-A suggests that competition exists between the genotypes. Competition may be due to disparities in virulence between genotypes, differences in fitness, such as rate of replication, or a combination of factors. In this study we investigated if DWV genotypes differ in their rate of accumulation in Australian honeybees naïve to both V. destructor and DWV, and if viral load was associated with mortality in honeybee pupae. We singly and co-infected pupae with DWV-A, DWV-B, and a recombinant strain isolated from a V. destructor tolerant bee population. We monitored viral accumulation throughout pupation, up to 192 hours post-injection. We found significant differences in accumulation, where DWV-A accumulated to significantly lower loads than DWV-B and the DWV-recombinant. We also found evidence of competition, where DWV-B loads were significantly reduced in the presence of DWV-A, but still accumulated to the highest loads overall. In contrast to previous studies, we found significant differences in virulence between pupae injected with DWV-A and DWV-B. The average mortality associated with DWV-B (0.4% ± 0.33 SE) and DWV-recombinant (2.2% ± 0.83 SE) injection were significantly less than observed for DWV-A (11% ± 1.2 SE). Our results suggest that a higher proportion of DWV-B infected pupae will emerge into adults, compared to DWV-A. Overall, our data suggest that low mortality in pupae and the ability of DWV-B to accumulate to higher loads relative to DWV-A even during co-infection may favor vector transmission by V. destructor, and may thus be contributing factors to the increasing prevalence of DWV-B globally.